eLEARNING - A CHANCE FOR SMALL AND MEDIUM SIZED ENTERPRISES - Ileana Hamburg; Christiane Lindecke; Judith Terstriep (FernUniversität Hagen, 2005)
eLearning through its flexibility and facility of access is seen as a major enabler of lifelong learning (LLL), as a catalyst of change and a chance for small and medium-sized enterprises (SMEs) to improve their business and to integrate into European market. But so far the eLearning in the context of vocational educational training has been mainly adopted by large enterprises, while only little activity can be observed in SMEs. The question arises what the chances and challenges for SMEs are and what is the experience with its usage. In this paper after a presentation of key issues in eLearning chances and challenges of eLearning for SMEs are discussed and experiences are exemplified by three EU-funded eLearning projects. The focus lies on the ongoing project ARIEL - Analysing and Reporting the Implementation of Electronic Learning in Europe - coordinated by the Institut Arbeit und Technik (IAT).